Local Therapy Improves Overall Survival in Patients With Newly Diagnosed Metastatic Prostate Cancer. Issue 6 (17th January 2017) - Parikh, Rahul R.; Byun, John; Goyal, Sharad; Kim, Isaac Yi
Abstract : BACKGROUND: The role of local therapy, in the form of radiation therapy (RT) or radical prostatectomy(RP), and its association on outcomes is not well established in patients with metastatic prostate cancer. METHODS: Using the National Cancer Database (NCDB), we evaluated patterns of care and outcomes among patients diagnosed with metastatic prostate cancer from 2004 to 2013 treated with local therapy (RP, intensity‐modulated radiation therapy [IMRT], or 2D/3D‐conformal radiation therapy [CRT]). The association between local therapy, co‐variates, and outcomes was assessed in a multivariable Cox proportional hazards model and Propensity score (PS) matching was performed to balance confounding factors. Survival was estimated using the Kaplan–Meier method. RESULTS: Among the 1, 208, 180 patients in the NCDB with prostate cancer, 6, 051 patients met the inclusion criteria. No local therapy was used in 5, 224 patients, while 622 (10.3%), 52 (0.9%), 153 (2.5%) patients received RP, IMRT, and 2D/3D‐CRT, respectively. Use of local therapy was associated with younger age (≤70), lower co‐morbidity score, lower T‐stage, Gleason score <8, node‐negative status, private, and Medicare insurance, higher income quartile, and treatment at comprehensive or academic/research programs ( P  < 0.05). Five‐year overall survival for patients receiving local therapy was 45.7% versus 17.1% for those not receiving local therapy ( P  < 0.01). In multivariate analysis, RP (HR = 0.51; 95%CI, 0.45–0.59, P  < 0.01) and IMRT (HR = 0.47; 95%CI, 0.31–0.72, P  < 0.01) were independently associated with superior overall survival. After PS‐matching, the use of local therapy (RP or IMRT) remained significantly associated with overall survival (HR = 0.35; 95%CI, 0.30–0.41, P  < 0.01). CONCLUSIONS: The use of RP and IMRT, to treat the primary disease, was associated with improvements in overall survival for patients with metastatic prostate cancer. We have identified patient‐specific variations in the use of local therapy that may be tested in subsequent prospective clinical trials to improve patient outcomes in this setting. Prostate 77: 559–572, 2017 . © 2017 Wiley Periodicals, Inc.